Performance of Three Boro Rice Varieties Under Different Levels of Nitrogen Application - Razib, Md Anamul Haque; Sarker, Ahamed Ullah; Sultana, Nadira; Islam, Mohammad Nazrul; Podder, Rakhi (Research in Agriculture Livestock and Fisheries, 2023)
A field exper iment was carr ied out to study the effect of levels of nitrogen on the performance of three Boro rice varieties e.g. cv. BRRI dhan28, cv BRRI dhan29 and cv. Surjomoni. The experiment comprised four levels of nitrogen viz. 0 kg N ha-1, 60 kg N ha-1, 120 kg N ha-1 and 180 kg N ha- 1 . The experiment was laid out in a randomized complete block design with three replications. The highest grain yield (4.23 t ha-1) was obtained from cv. BRRI dhan29 because of production of the highest number of both total tillers m-2 and effective tillers m-2. BRRI dhan28 produced higher grain yield (3.39 t ha-1) compared to that of Surjomoni (3.07 t ha-1). Application of 120 kg N ha-1 produced the highest grain yield (4.23 t ha-1) because of the production of the highest number of both total tillers m- ' and effective tillers m-2 in the t reatment . Appl icat ion of 180 kg N ha-1 produced the second-highest grain yield (3.70 t ha-1) and 0 kg N ha-1 produced the lowest grain yield (2.76 t ha-1). Interaction between variety and levels of nitrogen significantly influenced all parameters studied except plant height, total tillers hill -1, effective tillers hill-1, non-effective tillers hill-1, length of panicle, number of sterile spikelets panicle-1 and 1000-grain weight. The highest grain yield (4.60 t ha-1) was obtained from BRRI dhan29 with the application of 120 kg N ha-1 and the lowest grain yield (2.40 t ha- 1 ) was obtained f rom the treatment combination of Surjomoni and 0 kg N ha-1. Rice variety BRRI dhan29 can be provided with 120 kg N ha-1 to get the highest and economic production of the crop. Vol. 9, No. 3, December 2022: 267-278